Impact of farmer training on potato yield a case of smallholder potato farmers in Malawi - Kangogo, E.; Otieno, David Jakinda; Okello, J.J.; Mwenye, O.; Kapalasa, E. (Frontiers Media, 2024)
Due to rapid population growth, agri-food systems have been under increasing pressure to adapt and innovate to sustainably meet the growing demand for food. This requires advances in agricultural practices, technology and distribution networks. Farmer training has been proven to be a crucial component in this transformative process. Equipping farmers with the necessary knowledge and skills becomes paramount to optimize agricultural productivity while also improving their coping with the effects of climate change. This study applied the difference-in-difference method with inverse probability-weighted regression to analyze the impact of farmer training on potato yield. Results showed that 40% of farmers who received training interventions were members of farmer groups and had more farming experience compared to the control group. Additionally, the annual crop enterprise revenue for training participants was USD 255 compared to USD 134 for the control group. Results also showed that potato farmers who participated in positive selection training reported an increase in yield by 14%. On average, training participants were able to increase their potato yield by 1.33 tons per acre. These findings demonstrate the importance of providing targeted training and specific skills in order to enhance farm output. Furthermore, improving access to credit and supporting effective participation in farmer groups would increase farm yields.